Improving Self-regulation in a MOOC Environment - Stefanos, Giasiranis (Research Aspects in Arts and Social Studies Vol. 7, 2023)
MOOCs are a new distance education proposition offering the possibility of obtaining university education knowledge even from well-known universities such as Harvard and MIT. However, their educational value is questioned as a very small percentage of those who enroll manage to complete them. One way to improve this situation is to strengthen the self-regulatory characteristics of the participants. In this research we tried to strengthen the degree of self-regulation of the participants who took part in the 8-week program on " Violence and bullying in schools " by following the processes of Zimmerman's cyclic model of self-regulation combined with the self-regulation strategy Mental Contrasting with Implementation Intentions (MCII). The two research groups were able to enhance their degree of self-regulation, the research group more, and successfully complete the program at a rate of 80.2%. This result shows that self-regulation is not the only factor that positively contributes to the successful completion of a MOOC program. The educational design of the program, its content and its organization still play a very important role. These results can be useful in the design of future MOOCs programs.